Pseudomonas lalkuanensis sp. nov., isolated from a bacterial consortia of contaminated soil enriched for the remediation of e-waste. Issue 12 (11th December 2020) - Thorat, Vipool; Kirdat, Kiran; Tiwarekar, Bhavesh; DaCosta, Elaine; Debbarma, Prasenjit; Shouche, Yogesh; Sathe, Shivaji; Goel, Reeta; Lodha, Tushar; Yadav, Amit
Abstract : A novel e-waste-degrading strain, PE08 T, was isolated from contaminated soil collected from a paper mill yard in Lalkuan, Uttarakhand, India. Strain PE08 T was Gram-stain-negative, rod-shaped, aerobic, oxidase-positive and catalase-positive. Optimum growth was observed at 30 °C (range, 5–40 °C), with 1–2 % NaCl (range, 0–3 %) and at pH 7 (range 6–11). The phylogeny based on 16S rRNA gene sequences delineated strain PE08 T to the genus Pseudomonas and showed highest sequence similarity to Pseudomonas furukawaii KF707 T (98.70 %), followed by Pseudomonas aeruginosa DSM 50071 T (98.62 %) and Pseudomonas resinovorans DSM 21078 T (97.93 %). The genome of strain PE08 T was sequenced and had one scaffold of 6056953 bp, 99.84 % completeness and 182× coverage were obtained. The G+C content in the genome was 64.24 mol%. The DNA–DNA hybridization and average nucleotide identity values between strain PE08 T and its closely related type strain, P. resinovorans DSM 21078 T were below 34.8 % and 87.96 %, respectively. The phylogenetic analysis based on whole-genome sequence and concatenated GyrB and RpoB proteins revealed that strain PE08 T forms a district clade in the family Pseudomonadaceae . The predominant fatty acids were summed feature 8 (C18 : 1 ω7 c and/or C18 :1 ω6 c ), summed feature 3 (C16 : 1 ω7 c and/or C16 : 1 ω6 c ), C16 : 0 and C12 : 0 . The major polar lipids were diphosphatidylglycerol, phosphatidylglycerol and phosphatidylethanolamine. The phenotypic, chemotaxonomic and genetic analysis, including overall genome relatedness index values, indicated that strain PE08 T represents a novel species of the genus Pseudomonas, for which the name Pseudomonas lalkuanensis sp. nov. is proposed. The type strain is PE08 T (=MCC 3792=KCTC 72454=CCUG 73691).